Economic Growth and Transition of Industrial Structure in East Asia - Kinugasa, Tomoko (Kobe University Social Science Research Series,, 2018)
This book explores new frontiers in the research of economic growth and industrial reconstruction, analyzing economic growth and transitions in industrial structure in East Asia with a variety of data. First, the effects of demographic change on trade openness is analyzed empirically using the panel data of APEC countries. Second, the determinant of wage and housing costs are estimated using survey data collected from peasant workers in China. Third, the determinants of conquests among nomads in or near China and dynasties from world history are analyzed empirically using data regarding dynasties. Fourth, critiques on Emmanuel's unequal exchange theory are investigated based on the profit data in the world. This book is highly recommended for readers who would like to obtain a new idea about economic development in terms of industrial structure.